INFLUENCE OF CONTEXTUAL FACTORS ON CUSTOMER EXPERIENCE MANAGEMENT AND ORGANIZATIONAL COMPETITIVENESS OF MOBILE TELECOMMUNICATION SERVICE PROVIDERS IN KENYA - Gecheo, P. Ooga; Thuo, J. Kuria; Byaruhanga, J. (IJRDO - Journal of Business Management, 2016)
One of the most important questions faced by business leaders in the strategic management processis a choice of how to adopt a market penetration strategy whereby a firm gains more usage fromexisting customers and also seeks to attract customers from existing competitors. The mobileservice industry has recently experienced a quick succession of mobile service innovations, indeciding on the optimal timing of each service launch, carriers need to consider a complex arrayof technological, regulatory, and strategic factors. In spite of wide-ranging research on marketpenetration strategy, very little empirical research has observed the relationship between themarket penetration strategies and competitiveness in mobile telecommunication sector. Based onthis background, this study sought to investigate market penetration strategy and competitivenessof mobile telecommunication service providers in Kenya. The study population consists of all themobile Service providers in Kenya which according to a list obtained from CommunicationsCommission of Kenya as at July 2010 are four. Given the small number of firms a census studywas conducted. The data for this study was collected from primary sources using a semi-structuredquestionnaire. The findings of the study revealed that contextual factors as extraneous variablesinfluence both the independent and the dependent variable directly. This study is significant sinceit is hoped that findings and recommendation of the study will provides a greater understanding ofappropriate contextual factors influences customer experience management and organizationalcompetitiveness. In this sense, the study will contributes to knowledge in terms of effectivestrategy implementation and its contribution to organizational performance.